2001
DOI: 10.2176/nmc.41.196
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Subdural Hematoma With Vasogenic Edema in the Cerebral Hemisphere. Case Report.

Abstract: An 80-year-old male with a history of hypertension presented with chronic subdural hematoma manifesting as progressive consciousness disturbance and left hemiparesis. T 1 -weighted and fluid attenuation inversion recovery (FLAIR) magnetic resonance imaging showed a fresh hematoma in the right subdural space with a midline shift of 15 mm. FLAIR and diffusion-weighted imaging showed a hyperintense area in the right paraventricular white matter compressed by the hematoma. Apparent diffusion coefficients (ADCs) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…While it is established fact that both diabetic ketoacidosis and CSDH &/subdural hygroma/ can cause tight brain /cerebral edema/ alone, the mechanism how cerebral edema occurs is different. That is, the direct mass effect of the CSDH &/subdural hygroma/ & indirect mass effect from vasogenic edema tend to compress the adjacent sulci, ventricles & basal cisterns and causes cerebral edema if the thickness is significant and it appears to result a proportionate level of brain tightness for the amount of CSDH in majority of cases [ 2 ]; while cytotoxic & vasogenic brain edema mechanisms from direct metabolic effects of DKA, water re-distribution effect of DKA & treatment related changes seen in DKA (see Fig. 1 ) are responsible for cerebral edema from DKA [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…While it is established fact that both diabetic ketoacidosis and CSDH &/subdural hygroma/ can cause tight brain /cerebral edema/ alone, the mechanism how cerebral edema occurs is different. That is, the direct mass effect of the CSDH &/subdural hygroma/ & indirect mass effect from vasogenic edema tend to compress the adjacent sulci, ventricles & basal cisterns and causes cerebral edema if the thickness is significant and it appears to result a proportionate level of brain tightness for the amount of CSDH in majority of cases [ 2 ]; while cytotoxic & vasogenic brain edema mechanisms from direct metabolic effects of DKA, water re-distribution effect of DKA & treatment related changes seen in DKA (see Fig. 1 ) are responsible for cerebral edema from DKA [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,14,19,22) We recently confirmed that diffusion-weighted imaging showed solid clots as high intensity areas in patients with traumatic subacute subdural hematoma 10) and organized subdural hematoma, 11) and measurement of the apparent diffusion coefficient (ADC) values was useful for differentiating solid from liquid components. 11) However, the diffusionweighted imaging appearance of chronic subdural hematomas has been rarely reported, 9) and the potential of diffusion-weighted imaging for the evaluation of chronic subdural hematoma has not yet been established.…”
Section: Introductionmentioning
confidence: 99%